1960
DOI: 10.1177/00220345600390050901
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations in Dental Development. I. Interrelationships within the Dentition

Abstract: At the present time, as a result of recently published data,"1 2 it is possible to make a quantitative evaluation of the extent to which a posterior mandibular tooth is advanced or retarded in its formation or eruption. Such a determination, however, is of limited value until its predictive significance is known. One may ask whether advancement or retardation in the formation of one tooth is necessarily indicative of the developmental status of other teeth and whether dental advancement at one age is necessari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Garn et al (1958), studying the mandibular premolars and molars of 255 children from the Fels longitudinal growth series, found girls to be advanced in dental development compared with boys, but by only 3% on average, and there was at least three times as much difference in skeletal maturation for those centers compared. Again using the Fels series, Garn et al (1960) found tooth calcification and tooth movement to be partially autonomous processes. For example, the correlation between alveolar eruption and apical closure for P1 was 0.52 and for P2 was 0.71.…”
Section: Dental Development Studies: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…Garn et al (1958), studying the mandibular premolars and molars of 255 children from the Fels longitudinal growth series, found girls to be advanced in dental development compared with boys, but by only 3% on average, and there was at least three times as much difference in skeletal maturation for those centers compared. Again using the Fels series, Garn et al (1960) found tooth calcification and tooth movement to be partially autonomous processes. For example, the correlation between alveolar eruption and apical closure for P1 was 0.52 and for P2 was 0.71.…”
Section: Dental Development Studies: Generalmentioning
confidence: 99%
“…Chronological ages were recorded in decimal years, calculated as date of film minus date of birth. Dental scores and dental ages were calculated and assigned for each film based on the Bengston (1935) Variation in eruption, especially canines and premolars Brauer and Bahador (1942) Calcification distinct process from eruption Gleser and Hunt (1955) Calcification more meaningful measure than emergence; M1 growth spurt at one-third completed root length Garn et al (1958) Sex difference in skeletal maturation greater than dental Garn et al (1960) Tooth calcification and movement partially autonomous Nolla (1960) No sex difference in length of total tooth development Grøn (1962) Majority of teeth erupt at three-quarters root complete Moorrees et al (1963a) Canine has proportionally longer roots than do premolars at emergence; increased velocity of root elongation near emergence Moorrees et al (1963b) Sex difference in root maturation (longer for males) Steel (1965) Nonsignificant developmental correlations among P2, M2, and M3 Haavikko (1970) Large cross-sectional study of dental development and eruption, Helsinki Gustafson and Koch (1974) Diagrams for four stages of dental development Anderson et al (1975Anderson et al ( , 1976 and Thompson et al (1975) Canine shows greatest sex difference; boys more variable; canine mineralization delay, males, 20%; no acceleration of dental mineralization during puberty; dental development correlates more strongly with morphological than with skeletal maturation Demirjian and Levesque (1980) Sex differences in dental development and emergence Feasby (1981) Report of ''eruption surge'' not well correlated with increased root length Moorrees and Kent (1981) MZ twin root attainment age correlations of 0.90 Dean (1985) Root cone angles measured; suggestion of faster rate of increase in root length as root extends Harris and McKee (1990) Root development more sexually dimorphic than crown development Mappes et al (1992) Intersample dental mineralization differences despite hand-wrist ossification similarity Simpson and Kunos (1998) Modified Moorrees staging technique; root elongation of canine does not change in rate with emergence; rate of root formation of premolars more rapid later in development Liversidge et al (1999) Nonsignificant dental maturation differences between London Bangladeshi and Caucasian children …”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…In developing countries, as development increases so does dental caries and children are at the forefront of the disease disadvantage (Naidoo & Myburgh, 2007). The strongest association, however, emerges to occur between dental eruption and skeletal growth (Garn et al, 1960;Demirjian et al, 1985). Early under nutrition in childhood affects skeletal growth and results in decreased height.…”
Section: Introductionmentioning
confidence: 99%
“…The identification process can be performed either by comparing ante-and post-mortem dental records to establish (to a high degree of certainty) that the remains of a decedent [16][17][18] .…”
Section: A) Human Identificationmentioning
confidence: 99%